Response of Soybean (Glycine max (L.) Merrill) to Mineral Nitrogen Fertilization and Bradyrhizobium japonicum Seed Inoculation - Janusz Prusiński; Anna Baturo-Cieśniewska; Magdalena Borowska (Agronomy, 2020)
A growing interest in soybean cultivation in Poland has been observed in the recent years, however it faces a lot of difficulties resulting from a poorly understood effectiveness of plant nitrogen fertilization and from the introduction of Bradyrhizobium japonicum to the environment. The aim of the study was to evaluate the consistency of response of two soybean cultivars to three different rates of mineral N fertilization and two seed inoculation treatments with B. japonicum in field conditions over four years regardless of previous B. japonicum presence in the soil. A highly-diversified-over-years rainfall and temperature in the growing season do not allow for a definite statement of the differences resulting from seed inoculation and mineral N fertilization applied separately or jointly in soybean. A high sensitivity of the nodulation process to rainfall deficits was noted, which resulted in a decreased amount of B. japonicum DNA measured in qPCR and dry matter of nodules. ‘Annushka’ demonstrated a higher yield of seeds and protein, higher plants and the 1st pod setting. ‘Aldana’, due to a significant decrease in plant density, produced a higher number of pods, seeds per pod and the 1000 seed weight per plant. Both cultivars responded with an increase in the seed yield after seed inoculation with HiStick, also with an application of 30 and 60 kg N, as well as with Nitragina with 60 kg N.